Features of the temperature dependence of the photoconductivity of the base of Mn4Si7-Si- Mn4Si7 structures (Texas Journal of Engineering and Technology, 2022)
In this article the influence of infrared radiation and temperature on the parameters of higher silicides of manganese on the surface of silicon created on the basis of impurity manganese atoms is studied. It is shown the possibility of creating effective thermal converters and photodetectors based on structures